An analysis of ESL lexical bundles in learners' academic writing - Harniza binti Abd Razak (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
This study is an analysis of the production of lexical bundles among L2 learners. The data for the analysis were collected from 40 English as a Second Language (ESL) students' term papers from Universiti Teknologi Mara Terengganu. The study aims to find out the extent lexical bundles were used by L2 learners in their essays. The frequency of lexical bundles found in the essays was calculated, the types of the bundles were sorted according to their categories and the factors contributing to the use and the avoidance of lexical bundles were identified. The study shows that the L2 writers attempted to produce lexical bundles in their term papers but they were very limited. This may be attributed to cross linguistic influence. In terms of the functional type of bundles produced, the writers produced more referential bundles compared to stance bundles and discourse organizers. There was also evidence that there were students who avoided the use of lexical bundles in their essays. The factors that contributed to this avoidance were lack of exposure, fear of making mistakes and uncertainty. An important pedagogical implication of the study is that lexical bundles should be exposed or taught to students in formal classroom teaching in order to help students produce more understandable and quality writing.